The impact of dental care programs on healthcare system and societal outcomes: a scoping review - Abdulrahman Ghoneim; Arezoo Ebnahmady; Violet D'Souza; Kamini Kaura Parbhakar; Helen He; Madeline Gerbig; Sonica Singhal; Carlos Quiñonez (BMC, 2022)
Abstract Background Dental diseases have detrimental effects on healthcare systems and societies at large. Providing access to dental care can arguably improve health outcomes, reduce healthcare utilization costs, and improve several societal outcomes. Objectives Our objective was to review the literature to assess the impacts of dental care programs on healthcare and societal outcomes. Specifically, to identify the nature of such programs, including the type of services delivered, who was targeted, where services were delivered, and how access to dental care was enabled. Also, what kind of societal and healthcare outcomes have been attempted to be addressed through these programs were identified. Methods We conducted a scoping review by searching four databases, MEDLINE, EMBASE, CINAHL, and Sociological Abstracts. Relevant articles published in English language from January 2000 to February 2022 were screened by four reviewers to determine eligibility for inclusion. Results The search resulted in 29,468 original articles, of which 25 were included in the data synthesis. We found minimal evidence that answers our proposed research question. The majority of identified programs have demonstrated effectiveness in reducing medical and dental healthcare utilization (especially for non-preventive services) and avert more invasive treatments, and to a lesser degree, resulting in cost-savings. Moreover, some promising but limited evidence about program impacts on societal outcomes such as reducing homelessness and improving employability was reported. Conclusion Despite the well-known societal and economic consequences of dental problem, there is a paucity of studies that address the impacts of dental care programs from the societal and healthcare system perspectives. MeSH terms Delivery of Health Care, Dental Care, Outcome assessment, Patient acceptance of Health Care.